A framework-based approach towards development of online research progress tracking system at FTMSK / Khairul Ashraf Basul Hak - Basul Hak, Khairul Ashraf (2006)
This research project is about developing Online Research Progress Tracking System using Web-Application Framework in FTMSK. The objectives of the research are to identify the workflow of CS226 student research and focusing on requirement as well as the design of the prototype. Ethnography approach is chosen to as the researcher is also a participant in the research environment. For data gathering, contextual enquiry and questiormaire is selected to gather the requirement and prove the finding at the end of the research. In the end of research project period, researcher found out that the result is comply with the objectives and therefore, all the objectives in these research project have been achieved.